Consumer Willingness to Pay for The Purchase of Spicy Acid Catfish at Pondok Gurih Restaurant, Pekanbaru - Fitri Yuliasma; Trisla Warningsih; Darwis Darwis (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
This research was conducted at Pondok Gurih Restaurant, Pekanbaru which aims to calculate the value of the willingness to pay of consumers and to analyze the factors that affect the willingness to pay of consumers for the purchase of catfish spicy acid. This research can be used as information material for the restaurant to improve the quality and facilities for consumer demand. The research method used is a survey method that used primary data and secondary data. The data collection techniques through interviews. The sample in this study are consumers who eat at the restaurant and are willing to be interviewed. The number of respondents used in this study was 100 people. The data analysis method used in this research is logistic regression. The results showed that the average cost to be paid by consumers was IDR 87,410 with the lowest WTP value of IDR 40,000 and the highest was IDR 150,000. Then the variables that significantly affect the consumer's desire to pay are age, income, education, and product quality. The variables that did not have a significant effect were gender, service quality, and occupation. Suggestions for businesses are to continue to improve product quality.